BUDIDAYA TOGA DAN PEMBUATAN PUPUK KOMPOS SEBAGAI UPAYA PENINGKATAN PENGHASILAN WARGA DUSUN SALAKAN - Tri Siwi Nugrahani; Herman Budi Susetyo; Muhammad Iqbal Birsyada (DHARMA BAKTI, 2018)
Some residents in the Salakan Trihanggo sub-district of Gamping Sleman have yard land but not utilized. They also have unkempt chicken pets and chicken manure waste not used for fertilizer. Though the yard can be optimized by planting toga crops and chicken manure waste can be used as material for compostable fertilizer that can be sold and eventually increase income.The lack of knowledge and skills of Salakan villagers in the utilization of land for the cultivation of toga plants and the making of compost fertilizer raises the interest of the team to perform community service activities (PKM) by providing solutions that are conducting training and advisory skills of making compost and toga plant in the form of ginger and kencur. PKM method conducted by the team that is participatory actively and mentoring by giving counseling and training the practice of making compost and cultivation of family medicinal plants (toga) in the form of ginger and kencur. Activities are held for 6 months, from March to August 2018, until the writing of this activity is still ongoing. The activity was followed by 17 people consisting of members of RT community and youth group.